PENGARUH GOOD CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, KUALITAS AUDIT TERHADAP KINERJA KEUANGAN PADA SEKTOR MANUFAKTUR PERUSAHAAN CONSUMER NON- CYCLICALS YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Nur Defi Sapitri; Nur Asmilia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine the influence of Good Corporate Governance, Intellectual Capital and Audit Quality on Company Financial Performance. Good Corporate Governance is measured by Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, and Audit Committee, Intellectual Capital is measured using the Value Added Intellectual Capital (VAIC) model which has three components (physical capital, human capital, and structural capital), and Audit quality is measured by using all auditor services belonging to KAP The Big 4 Firms, while financial performance is measured by return on assets (ROA). The type of data used is quantitative research. The research sample was carried out using a purposive sampling method, namely selecting samples based on criteria determined by the researcher. Based on the purposive sampling method, 35 samples were obtained from 118 manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for 2018-2022. The analytical method used in the research is multiple linear regression analysis using the Eviews 12 program. The results of the research show that Good Corporate Governance (Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, Audit Committee) has no significant effect on Return On Assets, Intellectual Capital has a significant effect on Return On Assets. Apart from that, this research also shows that Audit Quality does not have a significant effect on Return On Assets.